The effects of family directed power mobility on self-care, mobility, and social function in very young children with severe multiple developmental impairments - Aceros, Juan; Cesar, Guilherme M.; Rodriguez, Ayshka; Lundy, Mary (Frontiers in Rehabilitation Sciences, 2025)
IntroductionChildren with impaired mobility often experience negative impact on overall development leading to depression, social isolation, and perceived lower quality of life.ObjectiveOur study explored the effects of Power Mobility Devices (PMD), in the form of modified ride-on toy cars with two distinct activation/steering technologies, on functional independent and social function in young children with severe multiple developmental impairments.MethodologyTwelve children (age range 12–54 months) with neuromuscular, musculoskeletal, and genetic diagnoses, and metabolic progressive diseases participated. Significant cognitive, visual, or communication impairment was not exclusionary. Two types of activation and steering modifications (proportional control joystick and line follower technologies) were provided. Paired samples t-test contrasted pre-post functional capabilities after three months of PMD use in both Pediatric Evaluation of Disability Inventory scales of Functional Skills and Caregiver Assistance, each with the subscales self-care, mobility, and social/cognitive.FindingsImprovements were observed in all three subscales for Functional Skills (significant 9.8% increase in self-care, 21.4% in mobility, and 17.5% social/cognitive) and Caregiver Assistance (significant 35.4% increase in self-care).ConclusionThese quantitative results support findings of previous studies analyzing qualitative data, suggesting that early power mobility interventions provide positive improvements in the quality of life of children with severe developmental disabilities.